2017
DOI: 10.1128/aem.00672-17
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase I Isoform Hrr25 Is a Negative Regulator of Haa1 in the Weak Acid Stress Response Pathway in Saccharomyces cerevisiae

Abstract: Haa1 is a transcription factor that adapts cells to weak organic acid stresses by activating the expression of various genes. Many of these genes encode membrane proteins, such as and How Haa1 is activated by weak acids is not clear. Here, we show that casein kinase I isoform Hrr25 is an important negative regulator of Haa1. Haa1 is known to be multiply phosphorylated. We found that mutations in lead to reduced Haa1 phosphorylation and increased expression of Haa1 target genes and that Hrr25 interacts with Haa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…The rapid translocation of Haa1 from the cytosol to the nucleus, where it activates the transcription of its target-genes in response to lactic ( Sugiyama et al, 2014 ) or acetic ( Swinnen et al, 2017 ) acids, is concomitant with a decrease in Haa1 phosphorylation levels ( Sugiyama et al, 2014 ). The casein kinase I isoform Hrr25 is an important negative regulator of Haa1, inhibiting this transcription factor’s activity by phosphorylation ( Collins et al, 2017 ). It was also demonstrated that the exportin Msn5, which preferentially exports phosphorylated cargo proteins, interacts with Haa1 being essential to its exit from the nucleus where its function as transcription factor takes place ( Sugiyama et al, 2014 ) ( Figure 5 ).…”
Section: Transcriptional Regulatory Network Controlling Adaptive Resmentioning
confidence: 99%
“…The rapid translocation of Haa1 from the cytosol to the nucleus, where it activates the transcription of its target-genes in response to lactic ( Sugiyama et al, 2014 ) or acetic ( Swinnen et al, 2017 ) acids, is concomitant with a decrease in Haa1 phosphorylation levels ( Sugiyama et al, 2014 ). The casein kinase I isoform Hrr25 is an important negative regulator of Haa1, inhibiting this transcription factor’s activity by phosphorylation ( Collins et al, 2017 ). It was also demonstrated that the exportin Msn5, which preferentially exports phosphorylated cargo proteins, interacts with Haa1 being essential to its exit from the nucleus where its function as transcription factor takes place ( Sugiyama et al, 2014 ) ( Figure 5 ).…”
Section: Transcriptional Regulatory Network Controlling Adaptive Resmentioning
confidence: 99%
“…Haa1 translocates from the cytoplasm to the nucleus during acetic acid or lactic acid treatment (20,33). However, it is unknown whether the nuclear localization of Haa1 is the major regulatory step for its activation.…”
Section: Resultsmentioning
confidence: 99%
“…Ace1 exists in the nucleus independently of the Cu status, and Cu(I) binding converts an inactive Ace1 to a functional protein capable of DNA binding and activating transcription (30,76,77). In contrast, Haa1 translocates from the cytoplasm to the nucleus by an as yet unidentified mechanism during weak acid stress (20,33). Haa1, which was localized in the nucleus in the msn5 Δ mutant, exhibited reduced stability (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, S. cerevisiae commonly encounters acid stress in industrial settings, which will greatly affect the redox balance in the cell and metabolite yields [16][17][18]. The acid stress response mechanism of yeast cells includes the following four aspects: (1) the cell membrane maintains the stability of intracellular pH by restricting the penetration of high levels of acid; (2) the cell membrane channel proteins that regulates transcription factors and acid transport maintains the intracellular stabilization of pH; (3) adenosine triphosphatase H + -ATPase (encoded by the PMA1 gene) on the cell membrane can hydrolyse ATP to produce energy, pumping protons out of the cell to maintain a normal neutral pH environment in the cell; and (4) maintaining the integrity and uidity of cell membranes by modulating fatty acid composition [13,19,20]. Among these processes, maintaining the stability of intracellular pH through the massive consumption of ATP in the cell is the most important, but the results obtained using this method will lead to intracellular acidi cation, thereby inhibiting cell growth and metabolism, especially for the TCA cycle, with the Crabtree effect having the most notable in uence [12,19,21].…”
mentioning
confidence: 99%